A New Model for Analysis of Customer Interaction Activities of City Tours Providing Organizations: Implementation to Selective Tours of Sofia, Bulgaria - Petkova, Elena (Turizam, 2020)
The aim of the article is to present a model of the activities of the city tour provider organizations, involving relations with customers (tourists). The activities involving customer interactions include relations before, during and after the city tours. The model has been implemented to analyze the city tours of Sofa, Bulgaria. The results revealed that tours in Sofia are characterized by a high degree of interactivity between personnel and customers, and customers themselves, involvement of partners and intensive use of technologies.